2017
DOI: 10.3892/mmr.2017.7391
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-rich blackcurrant extract inhibits proliferation of the MCF10A healthy human breast epithelial cell line through induction of G0/G1 arrest and apoptosis

Abstract: Blackcurrants (Ribes nigrum L., Grossulariaceae) possess a high content of anthocyanin polyphenols, which have been demonstrated to exhibit beneficial effects on health due to their antioxidant and anticarcinogenic prope-rties. The present study investigated novel functions of anthocyanin‑rich blackcurrant extracts (BCEs) in a healthy mammary epithelial cell line, MCF10A. The percentages of viable cells were 85, 75, 53 and 31% following exposure to 50, 100, 200 and 400 µg/ml BCE, respectively. The half‑maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Blackcurrants are reported to contain four anthocyanins: cyanidin-3-glucoside (C3G), cyanidin-3-rutinoside (C3R), delphinidin-3-glucoside (D3G), and delphinidin-3-rutinoside (D3R) [9]; D3R and C3R are anthocyanins specific to blackcurrant [10]. These anthocyanins are known to have many health benefits, such as suppression of inflammation [11,12,13], improvement of glucose metabolism [14,15,16] and promotion of cardiovascular health [17,18,19]. Furthermore, we previously reported that blackcurrant anthocyanins act as phytoestrogens both in vitro and in vivo [9,13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Blackcurrants are reported to contain four anthocyanins: cyanidin-3-glucoside (C3G), cyanidin-3-rutinoside (C3R), delphinidin-3-glucoside (D3G), and delphinidin-3-rutinoside (D3R) [9]; D3R and C3R are anthocyanins specific to blackcurrant [10]. These anthocyanins are known to have many health benefits, such as suppression of inflammation [11,12,13], improvement of glucose metabolism [14,15,16] and promotion of cardiovascular health [17,18,19]. Furthermore, we previously reported that blackcurrant anthocyanins act as phytoestrogens both in vitro and in vivo [9,13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Blackcurrants are reported to contain four anthocyanins: cyanidin-3-glucoside (C3G), cyanidin-3-rutinoside (C3R), delphinidin-3-glucoside (D3G), and delphinidin-3-rutinoside (D3R) [ 1 ]. Blackcurrant anthocyanins have a number of health benefits, such as improving blood flow and preventing breast cancer [ 1 , 2 ]. However, there have been no reports on their health benefits for the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Blackcurrant ( Ribes nigrum L.) contains high levels of anthocyanins, including cyanidin-3-glucoside, cyanidin-3-rutinoside, delphinidin-3-glucoside, and delphinidin-3-rutinoside [1]. These anthocyanins are reported to have some health benefits, such as in the prevention of breast cancer and reduction of inflammation and obesity [2,3,4]. Furthermore, blackcurrant contains various bioactive compounds and has been traditionally used in the treatment of various conditions, including rheumatic disease [5].…”
Section: Introductionmentioning
confidence: 99%